Passage, kitga, and parcha: А comparative study of the genres - A.Z. Khabibullina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The lyrical genres of Russian and Tatar poetry (passage, kitga, and parcha) have been compared. It should be noted that in the modern study of literature, particularly in comparative studies, these forms have never been analyzed from the point of view of their similarities and differences. The purpose of the present paper is to clarify the essence of these genres in the light of comparative poetics, as well as to explain their unique properties based on the works of Russian classical writers (A.S. Pushkin and A.A. Fet) and Tatar poets of the early 20th century (Därdemänd, S. Ramiev, and Sh. Babich). Our study confirmed that kitga as a genre of small poetic forms dating back to the traditions of the literatures of the East, if compared to the romantic passage, is more holistic and complete in terms of its meaning, in which philosophical themes and ideas hold a special position. In many ways, this feature of kitga poetics depends on the mindset of the Eastern poets: the eternal is revealed in the small, the single expresses the universal, i.e., an undoubted thing is perceived as the eternal law. In the romantic passage – a genre of classical Russian poetry – the idea of incompleteness, lyrical perspective, and being turned towards the future identified both the plot of works and their graphical organization. The latter is expressed through dots and graphic spaces in the first and last lines. This paper proves that in the Tatar literature another short form of poetry – the genre of parcha – is close to the romantic passage. Unlike kitga, it is more amorphous in the context of genre features; its graphicalorganization is also similar to the passage. In particular, the analysis of the lyric cycle of S. Ramiev's “Parchas of Lermontov's Poems” and Sh. Babich's short work “The Winds Blow” confirms this idea.